DIETARY QUALITY AND NUTRITIONAL STATUS OF ADOLESCENTS IN RURAL AREAS OF SIGI REGENCY, INDONESIA - Nikmah Utami Dewi; Shendy Krisnasari; Kiki Sanjaya; Nurui Aida (Universitas Airlangga, 2025)
Adolescence is a transitional period from childhood to adulthood, marked by various changes in different aspects of life. These changes can put adolescents at risk of experiencing nutritional problems. Central Sulawesi faces adolescent nutrition problems due to unhealthy eating patterns and a lack of dietary diversity. The nutritional status of adolescents in Central Sulawesi is also worse than the national average. Rural adolescents are thinner than urban adolescents because they have lower intake of energy, protein, and fat. Place of residence indirectly affects nutritional status during adolescence. This research was conducted in the rural area of Sigi Regency using a random sampling method with 154 adolescents participating in the study. The Mean Adequacy Ratio (MAR) is used to assess diet quality, and BMI/U measurement is used to determine the nutritional status of adolescents. Overall, the diet quality is still low. A MAR score of 56.1% indicates that the nutritional intake of adolescents is not yet optimal, with protein, fat, and carbohydrates at adequate levels, but vitamins A, B1, and C, as well as B9 and B12, are still low, indicating a potential deficiency in the body. The percentage of thin and obese adolescents exceeds the national figures. There is no difference in MAR among nutritional statuses.Comprehensive nutritional interventions are needed to improve the still low diet quality and the still low nutritional status.